Pelestarian Koleksi Langka di Perpustakaan Nasional Republik Indonesia - Sankara Pratika, Gede Sai; Haryanti, Ni Putu Premierita; Suhartika, I Putu (Jurnal Ilmiah D3 Perpustakaan, 2019)
ABSTRACT The purpose study is provide information for the readers regarding the preservation process of rare collections in the Republic of Indonesia National Library. This study uses descriptive qualitative research methods. The results of this study indicate that preservation of rare collections in the Republic of Indonesia National Library applies conservation that is in accordance with existing SOPs. Factors of rare collection damage in the Republic of Indonesia National Library due to environmental, human, biota and collection factors themselves. Preservation of rare collections carried out before damage occurs is to do maintenance for 3 months and once a year. Preservation of rare collections after damage has some stages. Keywords: Preservation, Rare Collection, Preservation of Rare Collections